Counter-Insurgency and Human Rights Violations in Nigeria - Kingsley, Akanni (2019)
In the conduct of counterinsurgency campaigns by government forces, human rights of the citizens of the States where insurgents operate are usually violated. For instance in the prosecution of the Boko Haram counterinsurgency in North-east Nigeria, the Nigerian military, Multinational Joint Task Forces and the Civilian Joint Task Force have been accused of committing gross human rights abuses and serious violations of international humanitarian law resulting in on-going casualties and further destruction of property. This paper examines the violations of human rights which take place in the conduct of counter-insurgency campaigns in any State, including Nigeria. The paper argues that in spite of the avalanche of international and domestic laws which regulate the conduct of warfare, particularly the rules of International Humanitarian Law (IHL) and International Human Rights (IHR) law, Nigerian security operatives and their international partners engaged in counterinsurgency have continued to commit gross abuses of human rights in the North-east Nigeria. The paper further argues that it is not possible to launch a successful counter-insurgency campaign without committing gross violations of basic human rights such as life, dignity of human person, liberty, private and family life, association and assembly as well as right to freedom of movement, if the rules of engagement and international best practices are observed religiously. In view of these findings, the paper recommends that government forces engaged in counterinsurgency should observe strictly the IHL rules and rules of engagement for military personnel as well as investigation and prosecution of culprits to serve as deterrent to violators. Keywords: Counter-insurgency, Human, Rights, Violations, Nigeria. DOI: 10.7176/JLPG/85-02 Publication date:May 31st 201